A concept of clean toilet from the Islamic perspective - Abdul Rahim, Asiah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
Islam is the official religion of Malaysia and more than half of the population is Muslim. As Muslims, the aspect of cleanliness is one of the most important and basic things that should be followed and practised in everyday life. Allah loves those cleanse themselves as quoted in the holy Qur'an.